Body iron status in blood donors in Erbil - AL Gaff, Mohamad Salih; AL Ani, Mouroge; Babka, Sanabil Slew (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and Objectives: Blood donation is a process by which an individual voluntarilydonates blood for humanitarian reasons, for storage in blood bank. The aim of this study is evaluation of iron status of blood donors in Erbil city. Methods: Over six months period ,489 healthy looking adult male attending Nanakaly hospital for blood disease in Erbil city north of Iraq, those divided into 1st time donors, multiple donors (2-4times/2year) and frequent donors(>4times/2year), blood samples for complete blood picture, serum iron parameters &serum ferritin level were performed. Results: Ninety one donor(18.6%)were found to have laboratory evidence of iron deficiency, all were repeated donors, (20.5%) among multiple donors increased to (26.7%) among frequent donors. iron deficiency was positively related to the frequency of blood donations(p<0.001).the frequency of early stages of iron deficiency was higher among multiple donors (store depletion 47.9%, iron deficient erythropoiesis (IDE) 47.9% ompared to 37.2% store depletion &44.2% iron deficient erythropoiesis (IDE) among frequent donor iron deficiency anemia (IDA) was higher among frequent donors(18.6%V4.2%p=0.01).mean cell volume (MCV) was inversely related to frequency of donation, emoglobin and Hematocrit (HB& PCV) showed no association with serum ferritin or with frequency of donations, however serum iron& transferrin saturation were positively associated with erum ferritin level. Conclusion: iron deficiency is common among repeated donors and worsens with increasing frequency of donations ,iron supplementation may be needed.